FLOKE-LIAPUNOV’S THEOREM FOR DIRAC’S TWO-PARAMETER SYSTEM WITH PERIODICAL COEFFICIENTS - Sahakian, G. H. (Proceedings of the YSU A: Physical and Mathematical Sciences, 2001)
In this work matriciant, matrix of monodromy are defined, their properties are considered and Floke–Liapunov’s theorem is proved for Dirac’s two-parameter system with periodical coefficients.